Os efeitos da perda de carga em síntese de redes de trocadores de calor - Silva, Fernanda Ribeiro Gaspar Branco da (1998)
This work presents a software package which performs the synthesis of heat exchangers networks as well as the detailed design of real world compatible heat exchangers. The network synthesis is obtained by using the Pinch Analysis methodology. This methodology generates networks from defined goals like: minimal number of heat exchanges units; minimal utilities requirements and minimal heat exchange area. After defining the goals the network synthesis is performed by using the Pinch Design Method. The detailed design of the heat exchangers is carried out by taking into account both the available drop and the incrustation factors for each equipment. The design of the shell side heat exchangers is based on the Bell-Delaware method. In order to demonstrate the relevance of the developed software, two examples from the literature plus na industrial problem are presented as case studies. The obtained results of the proposed methodology demonstrate the importance of inc luding the equipment design in the heat exchangers network synthesis.